?-Synuclein modifies mutant huntingtin aggregation and neurotoxicity in Drosophila. - Poças, G.M.; Branco-Santos, J.; Herrera, F.; Outeiro, T.F.; Domingos, P.M. (Human Molecular Genetics, 2015)
Protein misfolding and aggregation is a major hallmark of neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease (HD). Until recently, the consensus was that each aggregation-prone protein was characteristic of each disorder [?-synuclein (?-syn)/PD, mutant huntingtin (Htt)/HD, Tau and amyloid beta peptide/AD]. However, growing evidence indicates that aggregation-prone proteins can actually co-aggregate and modify each other's behavior and toxicity, suggesting that this process may also contribute to the overlap in clinical symptoms across different diseases. Here, we show that ?-syn and mutant Htt co-aggregate in vivo when co-expressed in Drosophila and produce a synergistic age-dependent increase in neurotoxicity associated to a decline in motor function and life span. Altogether, our results suggest that the co-existence of ?-syn and Htt in the same neuronal cells worsens aggregation-related neuropathologies and accelerates disease progression.